Transforming a Library: Strategies for Implementing a Liaison Program. Issue 4 (1st October 2016) - Luckert, Yelena
Column Editor's Notes: This column examines advances in public services internal and external to libraries. The focus is on how public services, such as instruction and education, programming, research consulting, and circulation evolve and impact users. The strength of the column is its broad, international focus and contributors are encouraged to explore issues and recent advances in public services relevant to their geographical region, as well as the larger, global audience. Interested authors are invited to submit proposals and articles to the column editor at andrea.falcone@ucdenver.edu ABSTRACT: This article discusses implementation of a full-scale liaison program at a large academic library. It details the process and steps taken to implement the program, assessment of liaison librarians, and practical implications on staff and services.